El sistema económico mundial y el desarrollo de comunidades locales - Stí¶hr, Walter (Revista EURE - Revista de Estudios Urbano Regionales, 1983)
In this articles, Stohr states that develpment has always been associated with spacial integration at various scales. In this way he analyses some factors (economic, political) historically envolved in this process and the role of local communities in it. In the vision of the author, local communities still constitute the center of influence of political, economic, social and environmental factors therefore development of these communities must be the prime objective in every development policy